Passengers for the war? : the involvement of New Zealand women in employment during the Great War, 1914-1918 : a thesis presented in partial fulfillment of the requirements for the degree of Master of Arts in History at Massey University - Luxford, Sarah (Massey University, 2005)
This thesis investigates the effect of the Great War upon the employment of women and the social issues that were raised by the employment of women. In recent years there has been an upsurge in both scholarly and public interest in the Great War and New Zealand's involvement in it. The focus has not solely been on military aspects of the war, and published works have also investigated topics such as the wartime experiences of New Zealand soldiers.1 1 See, for example, Christopher Pugsley, The Anzac Experience: New Zealand, Australia and Empire in the First World War, Auckland: Reed Publishing, 2004; Matthew Wright, Western Front: The New Zealand Division in the First World War, Auckland: Reed Publishing, 2005; Jock Phillips, Nicholas Boyack and E.P. Malone (eds), The Great Adventure: New Zealand soldiers describe the First World War, Wellington: Allen & Unwin/Port Nicholson Press, 1988; Glyn Harper (ed.), Letters from the battlefield: New Zealand soldiers write home, 1914-1918, Auckland: Harper Collins, 2001. Deborah Montgomerie has noted that the Great War is also a 'burgeoning topic of current graduate student research'.2 2 Deborah Montgomerie, 'Reconnaissance: Twentieth-Century New Zealand War History at Century's Turn', in the New Zealand Journal of History (NZJH), Vol. 37, No. 1, April 2003, p. 65. Public interest in the period has also increased - there has been a notable rise in the number of people attending Anzac day ceremonies, and the sentiment accompanying the return of the Unknown Warrior in 2004 further underlines the present public interest in New Zealand wartime history.3 3 An estimated 10 000 people paid their respects to the Unknown Warrior whilst he was lying-in-state, and approximately 100 000 people lined the streets of Wellington to watch the funeral procession of the Unknown Warrior in November 2004, see News From the Ministry, Ministry for Culture and Heritage, December 2004, p. 4. The Dominion Post reported that in 2005, 'New Zealanders turned out in record numbers at Anzac Day services', and the parade marshal for the Wellington service, John Meredith, stated that the 'turnout [for Anzac Day services] had grown remarkably in the past four or five years', see The Dominion Post, April 26, 2005, p. A5. Despite the growth of scholarly interest in the military aspects of the Great War, the history of New Zealand women and their involvement has thus far been neglected to a large extent. Women have often been relegated to token mentions in chapters in general New Zealand histories. Olssen barely mentions the role of women during the war in his chapter 'Towards A New Society', in The Oxford History of New Zealand, other than to note that the war 'enlarged opportunities for women in white-collar occupations'.4 4 Erik Olssen, 'Towards A New Society', in Geoffrey Rice (ed.), The Oxford History of New Zealand, 2nd ed., Auckland: Oxford University Press, 1992, p. 278. In Paradise Reforged: A History of the New Zealanders: From the 1880s to the Year 2000, Belich devotes a couple of paragraphs to the increase in the number of women working from the 1880s to the 1910s, however he does not investigate whether the war impacted on female employment patterns or attitudes towards women.5 5 James Belich, Paradise Reforged: A History of the New Zealanders From the 1880s to the Year 2000, Auckland: Allen Lane, The Penguin Press, 2001, pp. 143-44. Michael King does not address the issue of employment during the Great War in The Penguin History of New Zealand, instead focusing on the military actions of the New Zealand forces overseas, and the reaction of those at home to the casualties.6 6 Michael King, The Penguin History of New Zealand, Auckland: Penguin Books Ltd., 2003, pp. 295-304. The extensive New Zealand's Heritage series, published in the early 1970s, describes women's work during the Great War in just one of its articles, concluding that by the end of the war, women were 'still largely occupied in the same areas of employment' that they had been before the war.7 7 Anon., 'Women in the War', in New Zealand's Heritage: the making of a nation, Vol. 5, Part 74, 1973, pp. 2063-5. The social impact that the war had on New Zealand has not yet been fully addressed, possibly due to the complex nature of the issue - Olssen admits that the impact that the Great War had on society 'is not entirely clear'.8 8 Olssen, 'Towards A New Society', p. 278.
Keywords: Women, employment; New Zealand, history; Women in war; World War, 1914-1918